Randomized clinical trials : design, practice and reporting - Machin, David, 1939-; Fayers, Peter M. (Chichester, West Sussex, UK ; Hoboken, NJ : Wiley-Blackwell, 2010)
In this title the authors provide step-by-step coverage of recent advances and developments in clinical trial methodology.